TRANSLITERASI DAN ANALISIS TEKS NASKAH “SEJARAH BERDIRINYA TARBIYAH ISLAMIYAH” KARYA ABDUL MANAF - Afriyanda Putra (Universitas Andalas, 2011)
This article describes the translation and text analysis of “Sejarah Berdirinya Tarbiyah Islamiyah” written by Abdul Manaf. Analysis result shows, there were conflicts between Kaum Tua and Kaum Muda in Minangkabau. Kaum Tua are tarekat scholars and Kaum Muda are Islam reformer scholars. In those conflicts, Kaum Tua form an association called PERTI which to compete Kaum Muda schools.